Non-Muslim Students' Perceptions of the Al-Islam and Muhammadiyah Course at the FKIP UM Buton - La Ode Sahrin Djalia; Sulasri; Kaharun; Wulandari (Institute Journal and Publication Muhammadiyah University of Buton, 2025)
This study aims to explore the perceptions of non-Muslim students regarding the Al-Islam and Muhammadiyah Studies (AIK) course within the multicultural learning environment of the Faculty of Teacher Training and Education (FKIP) at Universitas Muhammadiyah Buton. Using a qualitative research method, data were collected through in-depth interviews and direct classroom observations involving both AIK lecturers and non-Muslim students from the Primary School Teacher Education Program. The findings reveal that non-Muslim students generally perceive AIK as an informative introduction to Islamic values and Muhammadiyah thought. However, some students find certain materials normative and less relevant to their beliefs, indicating the need for more inclusive and contextual teaching approaches. Furthermore, classroom dynamics and social interactions with Muslim peers are influenced by the level of tolerance fostered by lecturers and fellow students. This research aligns with previous studies emphasizing the importance of religious education that promotes interfaith understanding in multicultural settings. It concludes that AIK, when delivered with empathy, openness, and respect for diversity, can serve as a valuable medium for character building and interreligious tolerance.